Constructing Compound Tests (skill – Motor) For Some Artistic Skills Of Volleyball Premier Players - Saba, Ahmed; Sattar, Kahlil (Journal of Physical Education, 2018)
Constructing Compound Tests (skill – Motor) For Some Artistic Skills Of Volleyball Premier PlayersThe importance of the research lies in constructing tests (skill – motor) of some artistic volleyball skills. To achieve this aim, the researcher used the descriptive method. The subjects were (60) elite volleyball players who represent six volleyball clubs. Experts and specialists in the field of volleyball specified six tests. A pilot study was conducted to achieve reliability, validity and objectivity of the test. The data was collected and treated using proper statistical operations. The researchers concluded that the test has very good levels of reliability, validity and objectivity because it is based on scientific methods. Finally they recommended using these tests for player's evaluation and selection as well as constructing other compound tests on other age groups.Keywords: skill, motor, tests, volleyball